Is there a potential of circulating miRNAs as biomarkers in rheumatic diseases? - Prajzlerová, Klára; Šenolt, Ladislav; Filková, Mária (Genes & diseases, 2023)
MicroRNAs (miRNAs) are small non-coding single-stranded RNAs of about 22 nucleotides in length that act as post-transcriptional regulators of gene expression. Depending on the complementarity between miRNA and target mRNA, cleavage, destabilization, or translational suppression of mRNA occurs within the RISC (RNA-induced silencing complex). As gene expression regulators, miRNAs are involved in a variety of biological functions. Dysregulation of miRNAs and their target genes contribute to the pathophysiology of many diseases, including autoimmune and inflammatory disorders. MiRNAs are also present extracellularly in their stable form in body fluids. Their incorporation into membrane vesicles or protein complexes with Ago2, HDL, or nucleophosmin 1 protects them against RNases. Cell-free miRNAs can be delivered to another cell in vitro and maintain their functional potential. Therefore, miRNAs can be considered mediators of intercellular communication. The remarkable stability of cell-free miRNAs and their accessibility in body fluid makes them potential diagnostic or prognostic biomarkers and potential therapeutic targets. Here we provide an overview of the potential role of circulating miRNAs as biomarkers of disease activity, therapeutic response, or diagnosis in rheumatic diseases. Many circulating miRNAs reflect their involvement in the pathogenesis, while for plenty, their pathogenetic mechanisms remain to be explored. Several miRNAs described as biomarkers were also shown to be of therapeutic potential, and some miRNAs are already tested in clinical trials.
Keywords: Biomarker; Therapy; Rheumatic diseases; Diagnosis; miRNA